2000
DOI: 10.1063/1.1290927
|View full text |Cite
|
Sign up to set email alerts
|

NEP for a Kuiper Belt Object rendezvous mission

Abstract: 3Los Alamos National Luborato~, i% Alamos, NM 87545, poston@lanl.gov AbstracL Kuiper Belt Objects (KBOS) are a recently-discovered set of solar system bodies which lie at about the orbit of Pluto (40 AU) out to about 100 astronomical units (AU). There are estimated to be about 100,000 KBOS with a diameter greater than 100 km. KBOS are postulated to be composed of the pristine material which formed our solar system and may even have organic materials in them. A detailed study of KBO size, orbit distribution,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2000
2000

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…A simple orbital mechanics code was developed and used to analyze the requirements for a KBO rendezvous mission, and the results are reported elsewhere in thk symposium (Lipinski, 2000). That analysis showed that a KBO rendezvous could be achieved in 13.0 years with a 1000 kg science payload if the dry mass of the rest of the spacecraft (power, thrusters, navigation, communication, tankage, etc.)…”
Section: System Analysis 1mentioning
confidence: 99%
See 1 more Smart Citation
“…A simple orbital mechanics code was developed and used to analyze the requirements for a KBO rendezvous mission, and the results are reported elsewhere in thk symposium (Lipinski, 2000). That analysis showed that a KBO rendezvous could be achieved in 13.0 years with a 1000 kg science payload if the dry mass of the rest of the spacecraft (power, thrusters, navigation, communication, tankage, etc.)…”
Section: System Analysis 1mentioning
confidence: 99%
“…All three systems use the same assumed low-mass deployable thermal radiator to maximize the conversion efficiency. Subsequent sections describe the options in more detail, and examples for the KBO mission are given in a companion paper in this conference (Lipinski, 2000). There has not been sufficient detailing of the designs to perform an accurate weight estimate for each system, but rough estimates indicate that all of these systems have the potential to have specific masses less than 35 kg/kWe.…”
Section: Tug Designmentioning
confidence: 99%